Molecular Topology Index of a Zero Divisor Graph on a Ring of Integers Modulo Prime Power Order - Satriawan, Didit; Aini, Qurratul; Abdurahim; Maulana, Fariz; Wardhana, I Gede Adhitya Wisnu (Universitas Airlangga, 2024)
In chemistry, graph theory has been widely utilized to address molecular problems, with numerous applications in graph theory and ring theory within this field. One of these applications involves topological indices that represent chemical structures with numerical values. Various types of topological indices exist, including the Wiener index, the first Zagreb index, and the hyper-Wiener index. In the context of this research, the values of the Wiener index, the first Zagreb index, and the hyper-Wiener index for zero-divisor graphs on the ring of integers modulo a prime power order will be explored through a literature review and conjecture.